The World of Eastern Orthodoxy - Chrissidis, Nikolaos A. (The Oxford Handbook of Early Modern European History, 1350-1750, 2015)
The chapter traces the development of Orthodoxy by focusing on the Ecumenical Patriarchate of Constantinople and the Russian Orthodox Church in the early modern period. It is based on the premise that in both cases Orthodoxy faced three main challenges: imperial/political, intellectual, and financial. In both the Ottoman and the Russian empires, the Orthodox Church played important roles in the political, administrative, cultural, economic, ideological, and social lives of the Orthodox believers. Orthodoxy usually provided legitimizing ideological support to state authority, was forced to reckon with Western cultural and theological trends, and also proactively defended its economic interests. For most of the period, the Ecumenical Patriarchate and the Russian Orthodox Church maintained constant contacts, even in the face of mutual suspicions of each other’s motives. The chapter argues that early modern Orthodoxy proved adaptive, developed over time, and withstood the challenges it faced, ultimately keeping its symbolic capital largely intact.
Citation Key Alias: lens.org/025-896-017-121-207
Keywords: dept.his